Wire Rope Sling Failure Analysis: Technical Root Causes, Investigation Methodology Critique, and Lessons for Lifting Safety and Organizational Learning - Ahmad Zaky; Yudha Pratesa; Johny Wahyuadi Mudaryoto (MBI, 2025)
Wire rope slings are critical in heavy lifting operations, yet their failure remains a persistent safety concern. This paper presents a case study of a catastrophic sling rupture that occurred during a heavy lifting trial, despite the lift being within its rated capacity. A multi-faceted failure analysis identified hidden corrosion fatigue at the sling’s ferrule and an unanticipated extreme overload condition as the primary technical root causes. Procedural and organizational factors—including inadequate risk assessment, deviation from critical lift protocols, and failure to act on prior lessons—also contributed to the incident. The contractor’s investigation is critically reviewed against best-practice Root Cause Analysis guidelines, highlighting both strengths and gaps in its methodology. Key lessons to improve lifting safety are discussed, such as implementing rigorous inspection and retirement criteria for aging slings and ensuring comprehensive lift planning. Overall, the case underscores the importance of robust investigation practices and effective organizational learning to prevent similar failures in the future.